Integrated bulk RNA and single-cell analysis with experimental validation reveal oxidative stress-related diagnostic biomarkers for osteoporosis. - Cheng Zhong; Liping Zhong (PLoS ONE)
Osteoporosis (OP) is a systemic skeletal disorder characterized by reduced bone mass and deterioration of bone microarchitecture, which increases fracture risk and impairs physical function. This study explores the role of CHRM2 in osteogenic differentiation and evaluates its potential as a biomarker for OP. Single-cell RNA sequencing revealed distinct differences in cell type distributions between OP patients and healthy controls, notably an increase in M1 macrophages and regulatory T cells in OP patients. Functional enrichment analysis underscored the involvement of regulatory T cells in OP pathogenesis. Furthermore, CHRM2 was identified as a key gene associated with oxidative stress. In vitro experiments demonstrated that CHRM2 knockdown enhanced osteogenic differentiation while suppressing cell proliferation, likely via interactions with COL4A2. These findings suggest that CHRM2 plays a negative regulatory role in osteogenic differentiation and may serve as both a diagnostic biomarker and a potential therapeutic target for early-stage OP.